2019
DOI: 10.1007/s00439-019-02016-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of placental genes linked to selective intrauterine growth restriction (IUGR) in dichorionic twin pregnancies: gene expression profiling study

Abstract: A linkage of dichorionic (DC) twin pregnancies with selective intrauterine growth restriction (IUGR) to alterations in placental gene expression is unclear. The aim of the study was to identify placental genes related to hypoxia, adipogenesis and human growth which may contribute to IUGR development. The study group (IUGR/AGA) comprised dichorionic (DC) twin pregnancies, where the weight of the twins differed by > 15%; in addition, one twin was small for gestational age (< 10th percentile-SGA) (IUGR) while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Another example of a gene where differentially expressed transcripts can be identified in disease is the one coding for leptin (LEP). As expected, LEP was highly upregulated at the gene level in disease compared to control, confirming numerous previous observations, including from our group (Madeleneau et al 2015 ; Biesiada et al 2019 ). The alternative splicing profile of LEP showed that the first part of the gene (exons 1–2a) has a higher expression in diseased placentas as compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“…Another example of a gene where differentially expressed transcripts can be identified in disease is the one coding for leptin (LEP). As expected, LEP was highly upregulated at the gene level in disease compared to control, confirming numerous previous observations, including from our group (Madeleneau et al 2015 ; Biesiada et al 2019 ). The alternative splicing profile of LEP showed that the first part of the gene (exons 1–2a) has a higher expression in diseased placentas as compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“…Among them, F13A1 is related to the heat stress tolerance of pregnant ewes 68 , ARNTL indirectly affects the fertility of animals by affecting the circadian rhythm of the animal’s ability 69 , 70 . DNMBP has a role in membrane transport between the cell surface and the Golgi apparatus (through genetic similarity), and GLIS3 affects the development of organs, such as the fetal pancreas or thyroid 71 73 .…”
Section: Resultsmentioning
confidence: 99%
“…F13A1 improves heat stress tolerance of ewes 68 , while UQCRH protects the organisms from radiation-induced ovarian damage 67 , which is essential for sheep living in desert environments. As for CCDC178 and CNGA1, they are involved in immune repair 77 , 78 , while GLIS3 71 73 and GNAQ 76 are involved in stable fetal organ development. EEPD1 56 plays a role in maintaining the stability of embryonic genome replication.…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine growth restriction (IUGR) is a common pregnancy complication associated with significant adverse perinatal outcomes 1 . It is an important cause of perinatal morbidity and death, 2 affecting 10%–15% of pregnant women worldwide 3 . IUGR is closely related to malnutrition during pregnancy, infectious diseases, pregnancy‐induced hypertension, substance abuse, and teratogen exposures, 1 among which malnutrition during pregnancy is the most common cause of IUGR 3,4 .…”
Section: Introductionmentioning
confidence: 99%